Standard International Trade Classification Revision 3 (United Nations New YorkUS, 1986)
Classifies all commodities entering external merchandise trade. In respect of each basic heading provides - the SITC Rev.3; the code in respect of the corresponding heading of the harmonized commodity description and coding system (HS) or of the Customs Co-operation Council nomenclature; and the corresponding SITC Revision 2 codes.
DC